BCR:ABL1 levels at first month after TKI discontinuation predict subsequent maintenance of treatment‐free remission: A study from the "GRUPPO TRIVENETO LMC". (8th October 2022) - Di Giusto, Sara; Toffoletti, Eleonora; Bonifacio, Massimiliano; Binotto, Gianni; Miggiano, Maria Cristina; Calistri, Elisabetta; Stulle, Manuela; Ermacora, Anna; Stella, Rossella; Scaffidi, Luigi; D'Amore, Fabio; Scotton, Giorgia; et al.
Abstract: We analyzed BCR::ABL1 expression at stop and in the first month after discontinuation in 168 chronic myeloid leukemia patients who stopped imatinib or 2nd generation tyrosine kinase inhibitors (2G‐TKIs) while in sustained deep molecular response. Patients were divided among those who maintained response (group 1, n  = 123) and those who lost major molecular response (group 2, n  = 45). Mean BCR::ABL1 RNA levels 1 month after discontinuation were higher in group 2 than in group 1 ( p  = 0.0005) and the difference was more evident 2 months after stop ( p  < 0.0001). The same trend was found both for imatinib and 2G‐TKIs. A receiver operating characteristic (ROC) analysis to determine a threshold value of BCR::ABL1 at 1 month after discontinuation identified a cut‐off value of 0.0051%, with 92.2% specificity, 31.7% sensitivity and a likelihood ratio of 4.087. Abstract : We analyzed BCR::ABL1 expression at stop and in the first month after discontinuation in 168 CML patients stopping imatinib or 2G‐TKIs, dividing patients who maintained response (1, n  = 123) and those who lost MMR (group 2, n  = 45). Mean BCR::ABL1 RNA levels at 1 and 2 months after discontinuation was higher in group 2 than in group 1, with a similar trend for imatinib and 2G‐TKIs. A BCR::ABL1 value <0.0051% at 1 month after discontinuation was the stronger predictor of treatment‐free remission (92.2% specificity).